Life in Recovery in Australia and the United Kingdom: Do Stages of Recovery Differ Across National Boundaries?. Issue 4 (2nd October 2018) - Best, David; Savic, Michael; Bathish, Ramez; Edwards, Michael; Irving, Jamie; Cano, Ivan; Albertson, Kathy
ABSTRACT: The evidence is now clear that more than one half of those who have a lifetime addiction to alcohol or drugs will eventually achieve stable recovery. As documented in the Life in Recovery surveys and elsewhere, recovery often brings about positive changes across a diverse range of life domains. Although this suggests that there are some universal experiences of recovery, there has been a lack of comparative recovery research examining the variations in recovery experiences across different settings and cultures. Using a combined data set of the United Kingdom and Australian Life in Recovery surveys and the three-stage model of recovery, the authors compare life achievements at each stage across the two settings. There are differences in patterns of recovery, with elevated levels of ongoing mental health problems in Australia, and significant involvement with the criminal justice system in the United Kingdom, suggesting a contextual and structural role in understanding recovery pathways. The implications for policy and practice are reviewed around structural barriers and the role of social justice in advancing recovery models and pathways.